Hop-derived Humulinones Reveal Protective Effects in in vitro Models of Hepatic Steatosis, Inflammation and Fibrosis. - Mahli, Abdo; Thasler, Wolfgang E.; Biendl, Martin; Hellerbrand, Claus (Planta Medica, 2023)
Nonalcoholic fatty liver disease (NAFLD) is emerging as leading cause of liver disease worldwide. Specific pharmacologic therapy for NAFLD is a major unmet medical need. Recently, iso-alpha acids, hop-derived bitter compounds in beer, have been shown to beneficially affect NAFLD pathology. Humulinones are further hop derived bitter acids particularly found in modern styles of beer. So far, biological effects of humulinones have been unknown. Here, we investigated the effect of humulinones in in vitro models for hepatic steatosis, inflammation and fibrosis. Humulinones dose-dependently inhibited fatty acid induced lipid accumulation in primary human hepatocytes. Humulinones reduced the expression of fatty acid uptake transporter CD36 and key enzymes of (de novo) lipid synthesis. Conversely, humulinones increased the expression of FABP1, CPT1 and ACOX1, indicative for increased lipid combustion. Furthermore, humulinones ameliorated steatosis induced pro-inflammatory gene expression. Furthermore, humulinones significantly reduced the expression of pro-inflammatory and pro-fibrogenic factors in control as well as lipopolysaccharide treated activated hepatic stellate cells, which play a key role in hepatic fibrosis. In conclusion, humulinones beneficially affect different pathophysiological steps of NAFLD. Our data suggest humulinones as promising therapeutic agents for the prevention and treatment of NAFLD.
EVALuna2:536972